Tensile strength prediction of natural fiber and natural fiber yarn: Strain rate variation upshot. (2020) - Chokshi, Sagar; Gohil, Piyush; Lalakiya, Amul; Patel, Parth; Parmar, Amit
Abstract: Fibers are the main load-carrying member in composites. Hence, it is required to examine the behavior of fiber against different strain rate (SR). In present study, the behavior of natural fiber (NF) and Natural fiber yarn (NFY) is investigated by varying the SR at lower SR: 0.17 × 10 −4 s −1 to 1.25 × 10 −4 s −1 (crosshead speed (CHS): 0.1 to 0.75 mm/min) and higher SR: 1.25 × 10 −4 s −1 to 25.00 × 10 −4 s −1 (CHS: 0.75 to 20 mm/min) and measure its effect on tensile strength (TS). Here, the range is proposed for SR of lower SR and higher SR. NF: hemp fiber, sisal fiber and banana fiber and NFY: flax fiber yarn, bamboo fiber yarn and cotton fiber yarn are procured for the tensile testing. The mathematical models: exponential model (EM), linear model (LM), logarithmic model (LOM), polynomial model (PM) and power model (POM) are also proposed to predict the TS at different SR. The paper signifies the outcome as: TS increases gradually at lower SR and decreases gradually at higher SR; PM is advised to use in the prediction of TS at lower SR and higher SR for NF and NFY.